2007
DOI: 10.1093/qjmed/hcm066
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, but not the metabolic syndrome, predicts the severity and extent of coronary artery disease in women

Abstract: Diabetes, fasting plasma glucose and hypertension, but not the metabolic syndrome, were associated with severity of coronary angiographic findings in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
2
25
2
1
Order By: Relevance
“…In multivariate analysis, high triglycerides and low HDL were predictors of angiographically proven CAD. 8 In our study, we also observed a direct relationship between diabetes and CAD and no relationship with metabolic syndrome. We also confirmed the importance of triglycerides as a predictor of CAD.…”
Section: Discussionsupporting
confidence: 65%
“…In multivariate analysis, high triglycerides and low HDL were predictors of angiographically proven CAD. 8 In our study, we also observed a direct relationship between diabetes and CAD and no relationship with metabolic syndrome. We also confirmed the importance of triglycerides as a predictor of CAD.…”
Section: Discussionsupporting
confidence: 65%
“…Patients with MS are at increased risk of cardiovascular events (2-fold increase in cardiovascular outcomes, cardiovascular mortality, myocardial infarction and stroke, and a 1.5-fold increase in all-cause mortality) [3,4]. However, there is still a controversy about the association of MS with stable coronary artery disease (CAD) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study by Zornitzki et al, however, the authors did not find an association between the severity of coronary disease and the presence of MetSx [31]. Several differences between the 2 studies exist and might explain the non-congruent findings.…”
Section: Discussionmentioning
confidence: 84%